The challenge of managing dyslipidemia in patients with nonalcoholic fatty liver disease. (August 2012) - Bril, Fernando; Lomonaco, Romina; Cusi, Kenneth
Nonalcoholic fatty liver disease (NAFLD) is much more common than previously believed, affecting at least a third of the overall adults and two-thirds of obese subjects. The disease is strongly associated with the metabolic syndrome and Type 2 diabetes mellitus. Recent studies have shown that it may be also associated with cardiovascular disease. Among the many potential mechanisms for the association of NAFLD with cardiovascular disease, it is believed that abnormal lipoprotein metabolism plays a major role. Elevated plasma triglycerides, low HDL-cholesterol and increased apoB levels characterize dyslipidemia in NAFLD. Given the potential for dyslipidemia to increase cardiovascular disease in NAFLD, patients should be diagnosed early and treated aggressively. Paradoxically, most patients with NAFLD are denied lipid-lowering drugs as they frequently have elevated liver aminotransferases, and there is a perception of an increased risk of hepatotoxicity among clinicians treating these patients. We recommend starting low-dose statins with titration based on close monitoring, which overall appears to be safe, although there is a need for long-term studies. The available literature also suggests that fibrate therapy, with or without associated statin use, is, in general, well tolerated and safe. In summary, this review will address the clinical implications of dyslipidemia in NAFLD and the common dilemmas that healthcare providers face when lipid-lowering therapy is needed in these patients.